Concept of the perception of the environment proposed by Tim Ingold - Koczwara, Hanna; Wróblewski, Zbigniew (Studia Ecologiae et Bioethicae, 2019)
The main concern on this article is the reconstruction of the concept of the perception of the environment proposed by Tim Ingold, cultural anthropologist from Scotland. The first part of the article is the illustration of historical and theoretical background of the concept of perception of the environment where the basic theoretical assumptions of Tim Ingold’s environmental anthropology were introduced. The main points of the background knowledge are: the ecological approach to the visual perception of J. Gibson, the concept of Umwelt proposed by Jacob Johann von Uexküll, the dwelling perspective for environmental transformations of Martin Heidegger, the concepts of mind embodiment and extension. The reconstruction of the concept of perception of the environment is aimed at explication of three main ideas: the life in movement, dwelling perspective and new skill development. The second part of this article is focused on the applications of the concept of perception of the environment in two case studies: the forest perception and the ecological approach to the materials.